2019
DOI: 10.5812/aapm.95796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anesthetic and Gastrointestinal Complications of Endoscopic Retrograde Cholangiopancreatography

Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is an endoscopic method for treatment of many biliary diseases. With respect to rapid recovery and more patient comfort, this procedure is currently performed under light general anesthesia (GA) or conscious sedation. Objectives: The current study aimed to clarify that intravenous sedation or light general anesthesia can be performed without great fear of anesthesia related complications in ERCP patients and sedative doses of propofol can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Our study revealed that common findings of ERCP among studied patients were bile duct dilation (42.3%), filling defects (33.8%), and bile duct strictures (14.7%). These findings agree with the results of many works of literature, such as Hormati et al (21) cross-sectional study in Iran and Kröner et al (22) study in the USA, which reported common findings of ERCP were the findings of choledocholithiasis like bile duct dilation or strictures. In our study, the endoscopic sphincterotomy was done for (80.5%) of patients during ERCP, and the biliary or pancreatic duct stenting was done commonly by plastic stents (67%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study revealed that common findings of ERCP among studied patients were bile duct dilation (42.3%), filling defects (33.8%), and bile duct strictures (14.7%). These findings agree with the results of many works of literature, such as Hormati et al (21) cross-sectional study in Iran and Kröner et al (22) study in the USA, which reported common findings of ERCP were the findings of choledocholithiasis like bile duct dilation or strictures. In our study, the endoscopic sphincterotomy was done for (80.5%) of patients during ERCP, and the biliary or pancreatic duct stenting was done commonly by plastic stents (67%).…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that the mean age of patients who underwent ERCP was (53.1 years); 25% of them were in the age group 60-69 years, with a predominance of the female gender. These demographic characteristics are close to the results of Muslim et al (21) retrospective observational study on 545 patients who underwent ERCP in the Gastroenterology and Hepatology Center in Al-Diwaniyah city (Central Iraq) reported that a higher proportion of studied patients were in the age group 60-69 years with prevalent female gender (60.36%). In the current study, 85.5% of included patients were Kurdish, and 14.5% were Arabic.…”
Section: Discussionsupporting
confidence: 87%
“…The outcomes of ERCP under EDNAS are similar to those done under anaesthetist-directed sedation with lower or similar complication rates [ 16 ]. Hence, our study proves that endoscopist-directed sedation does not affect the efficiency of the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the clinical characteristics of the patients, it is important to emphasize that an ERCP is an essential surgical procedure in the diagnosis and treatment of a variety of pancreaticbiliary disorders, for example, for the assessment of cholelithiasis cases until neoplasms [1], as well as repair biliary stenosis.…”
mentioning
confidence: 99%